Entwicklungspfade städtischer Klimapolitik: Bedeutung von Schlüsselereignissen und Schlüsselakteur:innen für die Klimapolitik in Potsdam, Remscheid und Würzburg - Kristine Kern; Wolfgang Haupt; Stefan Niederhafner (disP - The Planning Review, 2022)
Our paper explores the climate pathways of the three mid-sized cities German of Potsdam, Remscheid and Würzburg. Particular emphasis was put on key events (e.g. disruptive events) and key actors (e.g. local decision-makers) that significantly influenced the development of local climate policy. The path analyses are based on the analysis of several key policy documents such as climate strategies and reports and 34 interviews with local actors from city administration and politics. Main results were that all three cities started tackle climate change strategically despite the absence of major disaster events. Furthermore, it emerged that key events driving local climate action were often not directly related to the topic of climate change but concerned other areas of city development in the first place. Lastly, the results suggest that the set of key actors advancing local climate policies should most favorably consist of powerful initiators and accelerators on the executive level, active, well-connected and third-party funds generating supporters within the city administration, and information brokers from science. Future research needs to focus on the interplay between these different key actors. Furthermore, there is a lack of research on mid-sized cities in Germany. There is a need for more case studies in German cities, particularly in those that have not been visible as forerunners. This applies particularly to cities with limited local capacities that have nevertheless managed to pioneer climate policies. Their successful strategies and approaches could serve as models for cities that have to work under similar conditions.
Keywords: 710